Trace fossils : concepts, problems, prospects - Miller, William (Elsevier, 2007)
This book serves as an up-to-date introduction, as well as overview to modern trace fossil research and covers nearly all of the essential aspects of modern ichnology. Divided into three section, Trace Fossils covers the historical background and concepts of ichnology, on-going research problems, and indications about the possible future growth of the discipline and potential connections to other fields. This work is intended for a broad audience of geological and biological scientists. Workers new to the field could get a sense of the main concepts of ichnology and a clear idea of how trace fossil research is conducted. Scientists in related disciplines could find potential uses for trace fossils in their fields. And, established workers could use the book to check on the progress of their particular brand of ichnology. By design, there is something here for novice and veteran, insider and outsider, and for the biologically-oriented workers and for the sedimentary geologists. * Presents a review of the state of ichnology at the beginning of the 21st Century * Summarizes the basic concepts and methods of modern trace fossil research * Discusses crucial background information about the history of trace fossil research, the main concepts of ichnology, examples of current problems and future directions, and the potential connections to other disciplines within both biology and geology.